2006
DOI: 10.1002/ddr.20158
|View full text |Cite
|
Sign up to set email alerts
|

Adrenal corticosteroids, their receptors and hypertension

Abstract: Mineralocorticoids and glucocorticoids are primarily synthesized in the adrenal cortex, and play key roles in mediating physiological responses under stressful conditions, such as lack of water or nutrients. Both types of corticosteroid elevate blood pressure and elevated levels of these steroids are found in hypertensive patients. The major mineralocorticoid and glucocorticoid in humans are aldosterone and cortisol, respectively. Aldosterone activates the mineralocorticoid receptor (MR) and cortisol the gluco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 122 publications
(116 reference statements)
0
3
0
Order By: Relevance
“…Previous studies have shown that glucocorticoids can affect insulin resistance, gluconeogenesis, liposynthesis, accumulation of visceral fat, vascular reactivity, vascular remodeling, renal sodium reabsorption, and blood pressure [59, 40, 41]. However, the mechanisms whereby glucocorticoids can cause hypertension in humans remain unclear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that glucocorticoids can affect insulin resistance, gluconeogenesis, liposynthesis, accumulation of visceral fat, vascular reactivity, vascular remodeling, renal sodium reabsorption, and blood pressure [59, 40, 41]. However, the mechanisms whereby glucocorticoids can cause hypertension in humans remain unclear.…”
Section: Discussionmentioning
confidence: 99%
“…However, the mechanisms whereby glucocorticoids can cause hypertension in humans remain unclear. Most evidence suggested that glucocorticoids increase blood pressure through the modulation of vascular structure and function, renal sodium reabsorption, and metabolic changes [59, 40, 41]. In this study, we examined whether pharmacological inhibition of 11 β -HSD1 decreases blood pressure through a natriuretic mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…In mammals, the adrenal glands are endocrine glands that are responsible for releasing hormones including corticosteroids (such as cortisol) and catecholamines (such as epinephrine and norepinephrine) (Hu and Bolten 2006;Fung et al 2008). Amino acids play many roles in the adrenal glands.…”
Section: Determination Of Amino Acids In Mouse Plasma and Adrenal Glamentioning
confidence: 99%